Cho `x+y =2` `x.y=-1` Tính `a x^2 +y^2` `b) x^3 + y^3` `c) x^4 +y^4` `d) x^5 + y^5` `e) x^6 + y^6`

Cho `x+y =2`
`x.y=-1`
Tính
`a x^2 +y^2`
`b) x^3 + y^3`
`c) x^4 +y^4`
`d) x^5 + y^5`
`e) x^6 + y^6`

1 bình luận về “Cho `x+y =2` `x.y=-1` Tính `a x^2 +y^2` `b) x^3 + y^3` `c) x^4 +y^4` `d) x^5 + y^5` `e) x^6 + y^6`”

  1. a)x^2+y^2
    =x^2+2xy+y^2-2xy
    =(x+y)^2-2.(-1)
    =2^2+2
    =4+2
    =6
    b)x^3+y^3
    =x^3+3x^2 y+3xy^2+y^3-3x^2 y-3xy^2
    =(x+y)^3-3xy(x+y)
    =2^3-3.(-1).2
    =8+6
    =14
    c)x^4+y^4
    =(x^2)^2+2x^2 y^2+(y^2)^2-2x^2 y^2
    =(x^2+y^2)^2-2.(xy)^2
    =6^2-2.(-1)^2
    =36-2.1
    =36-2
    =34
    d)(x^2+y^2)(x^3+y^3)=6.14
    =>x^5+x^2 y^3+x^3 y^2+y^5=84
    =>x^5+x^2 y^2 .(x+y)+y^5=84
    =>x^5+(xy)^2 .2+y^5=84
    =>x^5+(-1)^2 .2+y^5=84
    =>x^5+y^5+2=84
    =>x^5+y^5=82
    e)(x^2+y^2)(x^4+y^4)=6.34
    =>x^6+x^2 y^4+x^4 y^2+y^6=204
    =>x^6+x^2 y^2 (x^2+y^2)+y^6=204
    =>x^6+(xy)^2 .6+y^6=204
    =>x^6+(-1)^2 .6+y^6=204
    =>x^6+y^6+6=204
    =>x^6+y^6=198

    Trả lời

Viết một bình luận

Câu hỏi mới